Children Abandoning Parents: What about Legal Sanctions? - Yunanda Rahma Putri (Unnes Law Journal, 2019)
Obligations of care to parents from adult children (alimony) is an obligation of every child that should not be overlooked. If obligations are not complete with good cause neglected elderly. Surely such neglect will result in the emergence of a sanction for the child. However, the presence of sanctions for the actions of his apathetic children has not been widely known by the community . The neglected elderly people will be accommodated by the government in unit pelayanan lanjut usia, the government should guarantee economic security. In addition to the welfare of neglected elderly there are other important things that the government should take note that the protection of the elderly from wrong actions and arbitrary. The results showed that alimony obligation towards the parents of a child in Unit Pelayanan Sosial Lanjut Usia Wening Wardoyo Kabupaten Semarang has not met considering all the necessaries of life of beneficiaries has been borne by the government. For beneficiaries who still have children who are actually capable but abandoned that get into the unit should be subject to sanctions which can be a verdict asking the child to care for and maintain it self as a civil, ostracized, ridiculed and denounced by relatives in customary law and gets the barrier great to enter the gates of heaven in Islamic law, legal protection and welfare of beneficiaries in Unit Pelayanan Lanjut Usia Sosial Wening Wardoyo Kabupaten semarang have met with both proven by the various services and facilities received by the beneficiaries.